PENGEMBANGAN MODEL LINTASKUJITU DALAM PEMBELAJARAN MENYIMAK FABEL - Syafrina, Dewi; Nofitria, Anri (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
Listening learning haven’t received attention in planning lessons. Therefore, a model is needed that can apply listening principles in learning. This study developed the Lintaskujitu model for fables listening learning and described the results of the validation test and students' perceptions of the model implementation. The development research model used is 4D (define; design; development; disseminate). The expert of model and listening learning, and teacher were involved to validity test and 28 students became participants in implementation of Lintaskujitu model used quesionner. This research and development resulted in six stages of learning which are packaged in a guidebook. The Lintaskujitu model was declared feasible for implementation by experts and teacher with a percentage of 76% (the model concept), 79% (the model steps), and 75% (the level of student needs). Based on the results of this research and development, the Lintaskujitu model can be implemented in listening learning, especially in learning fables.